Physicochemical Properties of Bread with the Addition of Green Peas (Pisum sativum) - Alfonsus, Angelica Putri; Kwa, Audrey Laurelia; Hartono, Hudson; Widjaja, Kristophe Graciante; Josephine, Sheren Tania; Ariska, Desak Putu (Indonesian Journal of Life Sciences, 2024)
The objective of this study is to investigate the physicochemical characteristics of bread with the addition of green peas (Pisum sativum). In this study, three different treatments were done including 0% (control), 12.5% and 25% of green peas puree were added to the bread dough mixture and afterwards baked to analyze its physicochemical properties. Texture-wise, the addition of green peas did not show any significant effect (p>0.05) on the springiness of the bread yet it was otherwise for hardness, cohesiveness and chewiness. Moreover, the color of bread in different treatments have their own distinguishable details. Green peas had allowed the bread to become darker in color but the different amount of green peas puree added did not cause a change in the hues of the color. Furthermore, the moisture content of the bread added with the highest amount of green peas was shown to have the highest moisture content and the difference between the moisture content of each treatment was rendered to be significant (p≤0.05). Green peas seem to have caused a decrease in loaf volume and height due to the high amount of fiber contained in it. Nevertheless, the addition of green peas did not give any significant effect on the baking loss, loaf width and loaf length of the bread (p>0.05).